2018
DOI: 10.1097/cej.0000000000000410
|View full text |Cite
|
Sign up to set email alerts
|

Expression of KLF6-SV2 in colorectal cancer and its impact on proliferation and apoptosis

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…Early studies demonstrated that KLF6 is frequently inactivated in CRC [28]. A recent study revealed that the mRNA level of KLF-SV2 tended to be reduced in CRC tissues compared with that in adjacent non-tumor tissues [29]. Additionally, overexpression of KLF-SV2 markedly decreased the proliferation and enhanced the apoptotic rate of SW480 and SW620 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies demonstrated that KLF6 is frequently inactivated in CRC [28]. A recent study revealed that the mRNA level of KLF-SV2 tended to be reduced in CRC tissues compared with that in adjacent non-tumor tissues [29]. Additionally, overexpression of KLF-SV2 markedly decreased the proliferation and enhanced the apoptotic rate of SW480 and SW620 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they also found that KLF6-SV1 was significantly higher in young patients than in adult patients ( P =0.0003). Zhang et al 19 used qRT-PCR to detect wtKLF6, KLF6-SV1, KLF6-SV2 and KLF6-SV3 at the mRNA level in a total of 60 colorectal cancer (CRC) patients and found that the splice variants represented 1.5%–15.9% compared with wt KLF6, and SV1 mRNA expression was higher than SV2 and SV3 mRNA expression. The total, wild type, SV2 and SV3 of KLF6 were decreased except for SV1 expression increased in CRC samples.…”
Section: Discussionmentioning
confidence: 99%
“…Cell proliferation and apoptosis are regulated by multiple molecules and mechanisms that regulate the physiological or pathological growth of tissues and organs. The aberrant dynamic balance of cell proliferation and apoptosis leads to the occurrence of many diseases, such as polyps [ 19 , 20 ], precancerous lesions [ 21 ], and tumors [ 22 ]. In the present study, the finding that apoptosis and cell proliferation of cells derived from untreated nasal polyp tissue was increased has been supported by a previous study [ 3 ].…”
Section: Discussionmentioning
confidence: 99%